La Corte Suprema de Justicia bajo el gobierno del general Gustavo Rojas Pinilla (2014)
The paper explores the political role of the Supreme Court of Colombia during the government of General Gustavo Rojas Pinilla, particularly from 1953 to 1956. It deals with the relationship between the government of General Rojas and the Supreme Court during the abovementioned period, and the ways in which the military regime tried to affect the independence of the court at different times. The constitutional judicial review of decrees and constitutional reforms during the Rojas administration reveals the strategic behavior of the court, and the interdependencies between law and politics.